Etablering af en dansk historiografisk forskningstradition 1975-1985 - Raymond Jørgensen, Bent (Historisk Tidsskrift, 1994)
The 1970s and the first half of the 1980s witnessed a unique and benchmark profusion of intensive historiographical research and debate among Danish professional historians. It was extraordinary in three respects: 1) debate on the historical development of Danish historical research was in itself unusual; 2) the substance of research and debate critically dissociated itself from essential elements in the Danish professional tradition; 3) new, comprehensive approaches were proposed as alternatives to the »traditional« views. The present study has two main objectives: the first is to examine to what extent a new Danish historiographic tradition was established during the decade from 1975 to 1985; the second is to present an overview of the development of historiographic research in that period. Starting with an account of the international debate unleashed by Thomas S. Kuhn's conception of science and his fundamental view of its historical develop ment, the study shows that many of the objections levelled against Kuhn's paradigm model from the viewpoint of a theory of science are also employed in the Danish debate on the usefulness of the model in historiographic studies. Side 260 Actual attempts to apply Kuhn's conceptional apparatus to the study of Danish historiography exhibit considerable problems of adaption and operationalization.This is made clear, among other things, by great variation in the interpretationand use of the paradigm concept. The basic disagreement is on the question of whether the main emphasis - from the viewpoint of the sociology of science - should be put on internal or external explanatory factors. This is important for the periodization and description of the development of history research. The results of Tiemroth's thorough and stringent utilization of the paradigm concept may have given special impetus to a growing distrust of its applicability, because the description of long crisis situations and short periods of normal scientific research practice render the concept of normal science meaningless, and because the claim that Arup's History of Denmark represents the paradigm-consummating synthesis of the Erslev school stands in such stark contrast to the contemporaneous reaction to that extraordinary work. Nevertheless-and, in part, because of the influence of the paradigm debatethe principal impression of the period is persistently one of critical dissociation from the traditional concept of science, which had previously dominated the basic conception of the history of science and classical historiography. Furthermore, tendencies can be observed towards innovative thinking and a desire to converge on something new. There is, increasingly, a critical rejection of the idea that the development of research is guided almost exclusively by empiricalobjective and logically unassailable elements of cognition. This is matched by a growing understanding of and assent to the conception that research is an activity that takes place in a scientific community influenced both by its own internal conditions and by the political, economic and cultural conditions of its societal environment. The period also evidences greater skepticism towards the claim that scientific activity generates cumulative, continuous and almost automatic cognitive progress. The practical signs of these tendencies of the new historiographic research are manifested in part by the emphasis it places on the need to examine: 1) the entirety of a given historian's production, as opposed merely to theoretical and methodological expressions of self-understanding; the latter are readily available, but often at odds with actual practice; 2) the scientific production of entire schools or traditions, as opposed merely to the authorship of a single historian; and 3) the scientific community's and the societal environment's reciprocal influence. The extent to which one is disposed to see these traits as indications of a new historiographical tradition will depend on how narrowly the latter is defined. One should take note that no historiographer as yet has been able to fully abide by the precepts noted above, and that their observance in practice proves quite difficult. There is still no standard work that can be consulted, and the historiographical synthesis that might draw historiographers together has yet to appear. Moreover, it seems highly questionable that the lack of interest in historiography after 1985 can be said to represent »normal« research practice. Finally, innovative historiographic thinking could also be seen as a further logical development of the classical tradition. Translated by Michael Wolfe